The Effect of Intervention Approaches of Emotion Regulation and Learning Strategies on Students' Learning and Mental Health - Elodie Charbonnier PhD; Sarah Le Vigouroux PhD; Cécile Puechlong PhD; Lucile Montalescot PhD; Aurélie Goncalves PhD; Louise Baussard PhD; Beatrice Gisclard PhD; Antony G. Philippe PhD; Florence Lespiau PhD (SAGE Publishing, 2023)
University students are a vulnerable population, and many recent studies show that anxiety, depressive symptoms, and academic burnout have been on the increase since the beginning of the COVID-19 pandemic. These findings point to a need for interventions to reduce these difficulties. The purpose of the present study was to assess the effects of 2 formats of an innovative program on students' mental health (anxiety, depressive symptoms, and academic burnout), intolerance of uncertainty, learned helplessness, and learning. Our sample was composed of 105 university students, recruited on a voluntary basis. They were divided into 3 groups: online intervention group (n = 36), face-to-face intervention group (n = 32), and control group (n = 37). The following variables were measured through online questionnaires: anxiety and depressive symptoms, academic burnout, intolerance of uncertainty, learned helplessness, perceived social support, learning strategies, and beliefs. There were 2 assessments 10 weeks apart (ie, before and after the program in the case of the 2 intervention groups). We performed nonparametric analyses to run comparisons between the 2 assessment timepoints in each group. Results showed that participants in the 2 intervention groups had lower levels of learned helplessness and intolerance of uncertainty at the end of the program. Furthermore, participants in the face-to-face group reported higher levels of perceived social support, academic self-efficacy, and help-seeking strategies. The present study highlighted the benefits of our innovative program, especially its face-to-face format. Clinical Trial - ID: NCT04978194.